Haematopoietic Stem Cell Transplantation for Primary Haemophagocytic Lymphohistiocytosis - Lehmberg, Kai; Moshous, Despina; Booth, Claire (Frontiers in Pediatrics, 2019)
Review: Haematopoietic stem cell transplantation currently remains the only curative treatment of primary forms of haemophagocytic lymphohistiocytosis (HLH). Rapid diagnosis, efficient primary treatment of hyperinflammation, and conditioning regimens tailored to this demanding condition have substantially improved prognosis in the past 40 years. However, refractory hyperinflammation, central nervous system involvement, unavailability of matched donors, susceptibility to conditioning-related toxicities, and a high frequency of mixed chimaerism remain a challenge in a substantial proportion of patients. Gene therapeutic approaches for several genetic defects of primary HLH are being developed at pre-clinincal and translational levels.